The novel oral gonadotropin‐releasing hormone receptor antagonist relugolix is a new option for controlled ovarian stimulation cycles - Shinnosuke Komiya; Tomoko Tsuzuki‐Nakao; Yoshiko Asai; Tomoko Inoue; Yoshiharu Morimoto; Hidetaka Okada (Reproductive Medicine and Biology, 2022)
Abstract Purpose Relugolix is an oral gonadotropin‐releasing hormone antagonist (GnRHant), which was first introduced in 2019. This study investigated the effects of the conventional injectable GnRHant formulation and this new oral GnRHant formulation on controlled ovarian stimulation (COS) cycles. Methods Relugolix was administered in 126 cycles and conventional GnRHant injection was administered in 658 cycles (controls). The follicle stimulation was performed by an antagonist method, and for final oocyte maturation, recombinant human chorionic gonadotropin (rHCG), or gonadotropin‐releasing hormone agonist (GnRHa), or both (dual trigger) were selected. The number of retrieved oocytes was counted and then they were evaluated for subsequent development up to cleavage stage. Results The number of retrieved oocytes which was the primary outcome of this research was affected by the combination of GnRHant type and the final oocyte maturation agent. The combination of relugolix and a GnRHa trigger showed a significantly lower number of retrieved oocytes (p < 0.001) than the other combinations. Conclusions Relugolix is a new option for COS cycles, but should be carefully combined with the final maturation agent. Clinical trial approval This study was conducted after approval by the Medical Corporation Sankeikai Institutional Ethics Committee (approval number: 2019‐34).